Association of Nocturnal Hypoxemia with Progression of CKD - Sakaguchi, Yusuke (American Society of Nephrology, 2013)
BACKGROUND AND OBJECTIVES: Nocturnal hypoxemia is highly prevalent among patients with CKD. Nocturnal hypoxemia contributes to systemic inflammation, oxidative stress, endothelial cell dysfunction, and activation of the renin-angiotensin system, which are common pathologic mechanisms of CKD progression. This study investigated whether nocturnal hypoxemia is independently associated with CKD progression. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This two-center retrospective cohort study included 161 patients with stages 3–4 CKD enrolled from January of 2009 to July of 2011 with a body mass index less than 25.0 kg/m(2). The 4% oxygen desaturation index, the number of events per hour in which oxygen saturation decreases by >4% during sleep, was measured, and the declining rate of the estimated GFR was followed over 1 year. The severity of nocturnal hypoxemia was categorized as none (oxygen desaturation index<5.0), mild (5.0≤oxygen desaturation index<15.0), or moderate to severe (15.0≤oxygen desaturation index). RESULTS: The mean estimated GFR of the total cohort at baseline was 31 ml/min per 1.73 m(2). Eighty patients (49.7%) were diagnosed with nocturnal hypoxemia; 64 patients were diagnosed with mild nocturnal hypoxemia, and 16 patients were diagnosed with moderate-to-severe nocturnal hypoxemia. The estimated GFR declined three- to fourfold faster in patients with moderate-to-severe nocturnal hypoxemia than patients with no or mild nocturnal hypoxemia (the mean values [95% confidence intervals] were −2.14 [−1.06 to −3.21], −3.02 [−1.31 to −4.74], and −8.59 [−2.00 to −15.2] ml/min per 1.73 m(2) per year in the no, mild, and moderate-to-severe nocturnal hypoxemia groups, respectively; P=0.003). Nocturnal hypoxemia remained a significant predictor of decline in estimated GFR after adjustment for various baseline clinical factors. CONCLUSIONS: In nonobese patients with CKD, nocturnal hypoxemia is an independent risk factor of a rapid decline in kidney function.